COVID-19 vaccine hesitancy and attitudes toward routine vaccinations among Venezuelan migrants in Trinidad and Tobago: implications for a National Immunization Policy - Nyla Lyons; Brendon Bhagwandeen; Blair Gopeechan; Jeffrey Edwards (Frontiers Media S.A., 2024)
IntroductionVaccine hesitancy poses a threat to the prevention of COVID-19 and other vaccine-controlled diseases. In 2019, the Government of Trinidad and Tobago launched a policy outlining the scope of health services in the public sector available to registered Venezuelan migrants to include access to routine immunizations. Little is understood about immunization uptake among migrants, including the uptake of COVID-19 vaccinations in Trinidad and Tobago.MethodBetween July and October 2022, a survey was conducted using a sample of n = 507 Venezuelan migrants. We examined the relationship between COVID-19 vaccine hesitancy, migrant's attitudes toward past vaccinations, their beliefs and perceptions about COVID-19 disease, and health-service related factors. Descriptive statistics summarized the characteristics of these migrants. Odds ratios with 95% confidence intervals and multivariable logistic regression was used to examine factors and attitudes associated with COVID-19 vaccine hesitancy.ResultsOur findings showed that 89% of the migrants accessed publicly available health services while in Trinidad and Tobago, 72.4% reported that they did not refuse other vaccines in the past, and 23% reported being hesitant to take the COVID-19 vaccine. Females had higher odds of being COVID-19 vaccine hesitant compared to males, and participants expressing doubts about the source of vaccine information also had greater odds of vaccine hesitancy. Long waiting times at a public health clinic and costs associated with traveling to a clinic were associated with higher odds of COVID-19 vaccine hesitancy.ConclusionA National Immunization Policy inclusive of the unmet needs of vulnerable migrant populations is needed to ensure equitable access to vaccinations.